We Remember with Reverence and Love : American Jews and the Myth of Silence after the Holocaust, 1945-1962. - Diner, Hasia R. (NYU Press, 2009)
Winner of the 2009 National Jewish Book Award in American Jewish Studies. Recipient of the 2010 Guggenheim Fellowship in Humanities-Intellectual & Cultural History. It has become an accepted truth: after World War II, American Jews chose to be silent about the mass murder of millions of their European brothers and sisters at the hands of the Nazis. In this compelling work, Hasia R. Diner shows the assumption of silence to be categorically false. Uncovering a rich and incredibly varied trove of remembrances--in song, literature, liturgy, public display, political activism, and hundreds of other.